Stunting and associated factors among children aged 6-59 months from productive safety net program beneficiary and non-beneficiary households in Meta District, East Hararghe zone, Eastern Ethiopia: a comparative cross-sectional study - Aklilu Tesfaye; Gudina Egata (BMC, 2022)
Abstract Background Undernutrition is one of the major public health problems affecting children in developing settings. Despite impressive interventions like productive safety net program (PSNP), there is limited information on the association between stunting and PSNP implementation in Ethiopia. Methods Community-based comparative cross-sectional study design was used among systematically selected 1555 children and their mothers/caregivers from households enrolled in PSNP and not, respectively, in Meta District east Ethiopia from 5th-20th of March 2017. Data were collected using pretested structured questionnaire. Measuring board was used to measure length/height of children. Length/height for age Z-score was generated using World Health Organization (WHO) Anthro version 3.2.2. Descriptive statistics was used to describe all relevant variables. Bivariable and multivariable logistic regression analyses were used to identify predictors of stunting. Odds ratio along with 95% confidence intervals were estimated to measure the strength of association. The statistical significance was declared at p value less than 0.05. Results The prevalence of stunting was 47.7%, 95% CI (44.1%, 51.5%) and 33.5%, 95% CI (29.9%, 36.9%) among children from households enrolled in PSNP and non-PSNP ones, respectively. Lack of maternal education [AOR = 3.39; 95% CI (1.12, 5.11)], women's empowerment [AOR = 3.48; 95% CI (2.36, 5.12)] and fourth antenatal care visit [AOR = 4.2, 95% CI (2.5, 6.8)], practicing hand washing [AOR = 0.46; 95% CI (0.28, 0.76)], living in mid-land [AOR = 1.94, 95% CI (1.12, 3.35)] and low-land[AOR = 0.27: 95% CI (0.16, 0.45)] agro-ecological zones, PSNP membership [AOR = 1.82, 95% CI (1.14, 2.89)], childhood illness [AOR = 8.41; 95% CI (4.58, 12.76)], non-exclusive breastfeeding [AOR = 3.6; 95% CI (2.30, 4.80)], inadequate minimum dietary diversity [AOR = 4.7; 95% CI (3.0, 7.40)], child's sex [AOR = 1.73, 95% CI (1.18, 2.53)] and age (24-59 months) [AOR = 3.2; 95% CI (1.6, 6.3)] were independent predictors of stunting. Conclusions The prevalence of stunting was high among children from households enrolled in PSNP. Stunting was significantly associated with maternal- and child-related factors. Therefore, women empowerment on household's issues and improving infant and young child feeding practices could reduce the prevalence of stunting and its adverse consequences.